The Leuven Gymkhana: Transdisciplinary Action Research Questioning Socially Innovative Multi-Actor Collaborations in COVID Times - Medina-García, Clara; Nagarajan, Sharmada; Van den Broeck, Pieter (Frontiers in Sustainable Food Systems, 2022)
Literatures on social innovation, collective agency and multi-actor collaboration stress the importance of action research and joint problematization to research ongoing processes of collaboration and transformation and to advance both theory and practice in these fields. In this paper we share our experience building a transdisciplinary action research (TAR) trajectory between 2020 and 2021 to analyze socially innovative multi-actor collaborations (IMACs) and urban governance innovation trajectories in the city of Leuven (Belgium). We specifically focus on (1) how we involved a wide array of researchers, stakeholders and practitioners in the TAR trajectory; (2) how we enacted joint problematization and action, paying special attention ensuring that all facilitative leadership roles are taken care of; (3) the challenges that the specific COVID context posed on TAR and the innovative tools and approaches we took to adapt under such circumstances; and (4) how our TAR was a socially innovative practice in itself. We conclude that, when applied to research about IMACs, TAR becomes a case-study of IMAC in itself. Through this realization and the analysis of our experience, we get to broader question the role of action research and researchers in urban governance innovation. Further discussing our experience in relation to issues raised in action research literature, we summarize key dimensions, roles and tasks necessary in TAR to enable facilitative leadership and multi-actor collaboration and successfully drive joint problematization and transformative change. Not only are our learnings relevant for literature on socially innovative action research, governance innovation and multi-actor collaborations, but they also inform further action by the actors involved in the specific cases we were investigating.